Risk factors for the implementation of intrauterine adhesions in women of reproductive age - M. R. Orazov; L. M. Mikhaleva; S. Ya. Ismailzade (Медицинский вестник Юга России, 2022)
Childless marriages remain an important medical and social problem at present, both in our country and around the world. Infertility is a violation of the reproductive system, which has a wide range of conditions that affect one of the most important human functions – the ability to reproduce. The uterine factor of infertility occupies one of the leading positions in the formation of both primary and secondary infertility. Given the growth of acquired forms of uterine infertility, it is impossible not to turn to such a disease as intrauterine adhesions. Intrauterine synechiae is an acquired uterine disease that occurs after an injury to the endometrial mucosa. In the modern world, the prevalence of intrauterine adhesions in women of the reproductive period is increasing every year. However, it should be noted that despite modern technologies, it is impossible to accurately determine the number of women who have intrauterine adhesions. Taking into account the multifactorial development of intrauterine adhesions, as well as the low effectiveness of treatment methods, this problem occupies one of the leading positions in the structure of gynecological diseases and remains relevant. The asymptomatic course of the adhesive process leads to difficulty in diagnosis, and therefore the clinician needs to be aware of the risk factors for the development of intrauterine synechiae. The review presents risk factors for the formation of intrauterine synechiae.